Sexual identity management of working lesbian women - Kristine Khachatryan; Regine Graml; Tobias Hagen; Yvonne Ziegler; Ricky Astrida Herman (Organization Management Journal (OMJ), 2022)
Purpose - The purpose of this study is to provide a closer look at being out in the work environment. What are the characteristics that distinguish lesbian women who are out at work from those who are not? What role do companies play with their diversity-related measures? Design/methodology/approach - This paper investigates characteristics that distinguish lesbian women who were out at work and analyzes the use of various sexual identity management strategies in relation to specific reference groups within a company. Furthermore, the method of multiple correspondence analysis is used to visually map the associations between company-specific characteristics and being out. Findings - Results show that being out in the work environment is subject to a complex interplay of several factors, from personal resources to the diversity-friendliness of the company. A company's lesbian, gay, bisexual, transgender, and intersexual (LGBTI)-related measures, such as in-house LGBTI networks or diversity workshops, can not only promote the coming out of lesbian employees, and thereby help to increase their overall satisfaction with life, but can also reduce their experiences of discrimination. Originality/value - In this paper, the method of multiple correspondence analysis is used to examine the relationships between several diversity-related measures of the company and being out at the workplace. A visualization of these relationships in a two-dimensional space allows a more comprehensive view of these features and their possible effect on being out at the workplace.
Keywords: 650; Multiple correspondence analysis; Being out; Diversity sensitivity; Lesbian employee; Sexual identity management